Cultural diversity in the early childhood classroom in Australia: Educators' perspectives and practices - Buchori, Sylvia; Dobinson, Toni (University of Helsinki, 2012)
The steady change in demographics in a multicultural Australia has had significant implications for early childhood educators. This study, set in a multicultural early childhood setting in Australia, explored the different perceptions about cultural diversity and the pedagogic practices of a small staff of early childhood educators. Information was gathered via interview and participant observation and data was interpreted using a Miles and Huberman (1994) approach to data analysis. Findings suggested that (a) teachers viewed the cultural backgrounds that students brought with them as a burden (b) were preoccupied with achieving student conformity into the dominant culture and (c) lived very much in fear of their students falling below curriculum standards. Recommendations arising from the study focus on raising metacultural sensitivity (the ability to understand and assess one’s own culture and that of others at a deep level), incorporating more critical reflection upon pedagogy into teacher education courses, injecting more resources into schools dealing with cultural diversity and providing more formalised dialogue between teachers and parents from different cultural backgrounds.